The production and application of mind mapping for parents' education in the pediatric digestive disease clinic (小儿消化专病门诊家长教育思维导图的制作与应用) - LI Shaohan (李少晗); ZHU Zhenyun (朱振云); SHI Wenjuan (史文娟) (Association of Integrative Nursing, 2023)
Objective To produce a mind mapping for parents' education in the pediatric digestive disease clinic, and investigate its application value. Methods A total of 37 pediatric patients and their parents who attended to hospital between January and March 2021 were selected as the control group, another 45 pediatric patients and their parents who attended to hospital between April and June 2021 were recruited as the observation group. The control group received routine care and health education, and a mind mapping method was adopted for parents' education in the observation group. Parent's awareness of disease knowledge and satisfaction with nursing service were measures. Results The score of assessment on awareness of disease knowledge in the observation was higher than that in the control group (P＜0. 01). The score of nursing satisfaction scale in the observation was higher than that in the control group(P＜0. 01). Conclusion Application of mind mapping in health education is potentially effective to improve parents' knowledge level. (目的 制作小儿消化专病门诊家长健康教育的思维导图并应用, 探讨应用效果。方法 选取2021年1月-3月在小儿消化专病门诊就诊的37例患儿及其家长为对照组, 采用常规健康教育; 选取2021年4月-6月就诊的45例患儿及家长为观察组, 实施思维导图式的健康教育。评估家长对疾病相关知识掌握程度及护理满意度。结果 观察组患儿家长对疾病相关知识掌握程度评分高于对照组(P＜0. 01), 护理满意度评分高于对照组(P＜0. 01)。结论 将思维导图应用于小儿消化专病门诊健康教育中, 能有效提高患儿家长对疾病相关知识掌握程度。)